2005
DOI: 10.1016/j.jsgi.2005.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Up-regulated Angiogenin and Down-regulated Vascular Cell Adhesion Molecule-i Expression and Secretion in Human Placental Trophoblasts

Abstract: Because the primary defect in uteroplacental insufficiency is placental maldevelopment probably associated with hypoxia in situ, this study provides molecular evidence to indicate that the differential expression and secretion of angiogenic factors may play an important role in these pathologic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 54 publications
2
17
1
Order By: Relevance
“…Expression of ANG may be up-regulated in response to hypoxia within the tumor. A significant increase in the secretion and mRNA expression of ANG from both term placental explants and trophoblast cultures subjected to hypoxia in vitro was observed [21] . One study showed that ANG expression in invasive carcinomas is significantly positively correlated with HIF-1 alpha and the HIF-1 alpha target gene DEC-1 [22] .…”
Section: Discussionmentioning
confidence: 96%
“…Expression of ANG may be up-regulated in response to hypoxia within the tumor. A significant increase in the secretion and mRNA expression of ANG from both term placental explants and trophoblast cultures subjected to hypoxia in vitro was observed [21] . One study showed that ANG expression in invasive carcinomas is significantly positively correlated with HIF-1 alpha and the HIF-1 alpha target gene DEC-1 [22] .…”
Section: Discussionmentioning
confidence: 96%
“…The milieu of the trophoblast cells is characterized by hypoxia [18]. In addition, because vascularization is quite poor at the beginning of implantation, nutrient deprivation is not inconceivable.…”
Section: Discussionmentioning
confidence: 99%
“…CRL-1584), which has been used as the model for placenta in previous studies 2225 , was obtained from the Global Bioresource Center™ (http://www.atcc.org) and cultured in 10% MEM media (modified Eagle’s medium, GIBCO, USA; with 10% fetal bovine serum and antibiotics). The cultures were maintained at 37°C in an atmosphere of 5% of CO 2 .…”
Section: Methodsmentioning
confidence: 99%